Pluripotent stem cell models of Shwachman-Diamond syndrome reveal a common mechanism for pancreatic and hematopoietic dysfunction - Tulpule, Asmin (2013)
Shwachman-Diamond syndrome (SDS), a rare autosomal recessive disorder characterized by exocrine pancreatic insufficiency and hematopoietic dysfunction, is caused by mutations in the Shwachman-Bodian-Diamond syndrome (SBDS) gene. We created human pluripotent stem cell models of SDS by knock-down of SBDS in human embryonic stem cells (hESCs) and generation of induced pluripotent stem cell (iPSC) lines from two SDS patients. SBDS-deficient hESCs and iPSCs manifest deficits in exocrine pancreatic and hematopoietic differentiation in vitro, enhanced apoptosis and elevated protease levels in culture supernatants, which could be reversed by restoring SBDS protein expression through transgene rescue or by supplementing culture media with protease inhibitors. Protease-mediated auto-digestion provides a mechanistic link between the pancreatic and hematopoietic phenotypes in SDS, highlighting the utility of hESCs and iPSCs in obtaining novel insights into human disease.